2017
DOI: 10.1161/atvbaha.117.309539
|View full text |Cite
|
Sign up to set email alerts
|

ADAMTS13 Retards Progression of Diabetic Nephropathy by Inhibiting Intrarenal Thrombosis in Mice

Abstract: Objective ADAMTS13 (A Disintegrin And Metalloprotease with Thrombospondin type I repeats-13) prevents microvascular thrombosis by cleaving prothrombogenic ultra-large von Willebrand factor (ULVWF) multimers. Clinical studies have found association between reduced ADAMTS13 specific activity, ULVWF multimers and thrombotic angiopathy in patients with diabetic nephropathy. It remains unknown, however, whether ADAMTS13 deficiency or ULVWF multimers have a causative effect in diabetic nephropathy. Approach and Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…The prevention and treatment of DKD primarily include the control of blood glucose levels and the use of antihypertensive drugs, and an increase in blood pressure will further increase the rate of urinary albumin excretion[ 20 - 22 ]. Therefore, we assayed the hypertensive group to observe the effect of hypertension on the serum TNC level.…”
Section: Resultsmentioning
confidence: 99%
“…The prevention and treatment of DKD primarily include the control of blood glucose levels and the use of antihypertensive drugs, and an increase in blood pressure will further increase the rate of urinary albumin excretion[ 20 - 22 ]. Therefore, we assayed the hypertensive group to observe the effect of hypertension on the serum TNC level.…”
Section: Resultsmentioning
confidence: 99%
“…In a diabetic animal model, C-X-C motif chemokine ligand 1 (CXCL1) was found to possibly serve as a proinflammatory mediator 20 , 21 . In addition, VWF was reported to be involved in intrarenal thrombosis leading to the deterioration of renal function 22 . Purvis et al observed higher circulating plasma levels of ANXA1 in T1D and T2D patients, whereas the exogenous supplementation of ANXA1 improves insulin resistance and prevents the progression of subsequent microvascular complications in mice 23 , 24 .…”
Section: Discussionmentioning
confidence: 99%
“…All sections were de-paraffinized, re-hydrated and subjected to heat-induced antigen retrieval as described. 16,25 Briefly, sections were blocked with 5% serum at room temperature (RT), from the species in which the secondary antibody was raised. Endogenous peroxidase activity was quenched with 0.1% hydrogen peroxide in methanol for 15 minutes.…”
Section: Immunohistochemistrymentioning
confidence: 99%